Impaired acute metabolic responses to submaximal exercise in peripheral artery disease (PAD) - Lei Wang; Qian Zhu; Hongping Han; Huan Liu; Jin Wang (Vascular Medicine, 2026)
Background: Peripheral artery disease (PAD) is a prevalent manifestation of systemic atherosclerosis and is associated with substantial morbidity, impaired functional capacity, and adverse cardiovascular outcomes. Although reduced walking performance is a defining clinical feature of PAD, the underlying biological responses to acute physiological stress remain poorly understood. Methods: We conducted a prospective observational study including 35 patients with PAD and 36 control participants. All participants’ serum samples were collected immediately before exercise and 5 minutes after exercise. Acute metabolic responses were quantified using targeted liquid chromatography-tandem mass spectrometry. Functional assessments, between-group comparisons, and associations with disease severity were evaluated using nonparametric methods. Results: Compared with control participants, patients with PAD exhibited distinct alterations in exercise-induced metabolic responses. Hypoxanthine showed a robust postexercise increase in controls but a blunted and directionally opposite response in PAD ( p < 0.001), whereas 2-oxoglutarate increased significantly following exercise in PAD but not in controls ( p < 0.001). In exploratory analyses within the PAD group, exercise-induced changes in hypoxanthine and 2-oxoglutarate were not significantly correlated with ankle-brachial index (ABI) or 6-minute walk distance (6MWD) in the available cases. Conclusions: PAD is associated with impaired metabolic flexibility during acute exercise, characterized by altered purine- and tricarboxylic acid-related metabolic responses to exercise, supporting the concept that acute metabolic responses provide clinically relevant information beyond resting assessments in PAD.